2017
DOI: 10.1111/1471-0528.14949
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the progesterone receptor gene and susceptibility to recurrent pregnancy loss: a case–control study

Abstract: Genetic variants in progesterone receptor gene are associated with increased risk of recurrent pregnancy loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…1,2 We acknowledge that inclusion of data on tobacco usage (cigarettes, water pipe), vitamin D status, consumption of caffeine and alcohol, along with infection positivity [Mycobacterium tuberculosis, human papillomavirus (HPV)], as the clinically relevant covariates will strengthen the conclusion, as stated by Pandey et al 2 Smoking during pregnancy has long been associated with increased risks for miscarriage, preterm birth, and fetal morbidity and mortality.…”
Section: Authors' Replymentioning
confidence: 90%
See 1 more Smart Citation
“…1,2 We acknowledge that inclusion of data on tobacco usage (cigarettes, water pipe), vitamin D status, consumption of caffeine and alcohol, along with infection positivity [Mycobacterium tuberculosis, human papillomavirus (HPV)], as the clinically relevant covariates will strengthen the conclusion, as stated by Pandey et al 2 Smoking during pregnancy has long been associated with increased risks for miscarriage, preterm birth, and fetal morbidity and mortality.…”
Section: Authors' Replymentioning
confidence: 90%
“…The recently published article by Bahia et al 1 assessing the association of progesterone receptor (PGR) gene variants with susceptibility to recurrent pregnancy loss (RPL) provides critical clinical research insights in reproductive medicine. Pregnancy-related complications, including stillbirths, miscarriages and infertility, are emerging as major public health challenges among ethnically disparate populations worldwide, including women of Indian ethnicity.…”
Section: Sirmentioning
confidence: 99%
“…We agree with Pandey et al that a multi-centre collaborative study is warranted for assessment of the contribution of genetic variants in the progesterone receptor and progesterone signalling pathway, and probably for other sex hormones receptors also. Along with functional assays, transcriptomics, genomics, metabolomics and proteomics, this will be crucial in addressing the diagnostic/prognostic role for altered progesterone signalling in identifying RPL-susceptible women of diverse eth- Sir, The recent BJOG special edition on high-intensity focused ultrasound (HIFU) 1 provides refreshing topics for discussion about HIFU ablation for fibroids in reproductive women.…”
mentioning
confidence: 99%
“…Zou et al 1 reported retrospective data on 78 pregnancy outcomes in cases of fibroids treated by HIFU at a single centre, where 15 of the women delivered vaginally and 56 by caesarean section. They concluded that the pregnancy preparation time may be reduced by HIFU ablation, and fertility in women with infertility related to fibroids was improved.…”
mentioning
confidence: 99%
See 1 more Smart Citation